A novel five-level voltage source inverter interconnected to grid with srf controller for voltage synchronization - Bogimi Sirisha; Mohd Abdul Nazeemuddin (Institute of Advanced Engineering and Science, 2022)
Power utilization from renewable sources with efficient modules is very vital. Maitaining harmonics below specific standard during grid interconnection is also a major objective. A novel five-level voltage source inverter which is controlled by synchronous reference frame (SRF) controller for grid interconnection and synchronized power injection. The input of the converter is integrated with renewable energy source photovoltaic arrays (PVA) for the injection of renewable power into the grid. For constant voltage input, the PVAs are connected to a booster converter controlled by the maximum power point tracking (MPPT) algorithm. The design is analyzed with different operating conditions by changing the load type (static and dynamic) using MATLAB/Simulink software. Graphical comparisons are taken for the analysis with the help of ‘powergui’ toolbox available in the software.